The educational principles derived from the Surah Al- Furqan and its applications on family - Akram Al- Deen, Aisha Abdullah Ahmad (Journal of Educational and Psychological Sciences, 2020)
This study aimed to extract some educational principles derived on the side of creed, intellectual and moral, and their applications to the family through Surah Al- Furqan. The study followed the deductive method. The results of the study found that Surat Al- Furqan included the purposes and topics related to Islamic education, which can be beneficial from it, as well as Surat Al- Furqan contained many educational principles in various aspects including in the creed aspect like the principle of piety, faith, sincerity and trust. In the intellectual aspect the principle of think about the universal signs of Allah, consider the destruction of previous nations, remembrance. And on the moral side included the principle of humility, clemency, patience and abstention from the gossip, with explaining its applications in the field of family, in light of the results a number of recommendations and suggestions were like: need to search and learn the topics from the noble Qur’an, and translating it in different languages for the benefit on a large scale, Parents should take care of their children’s education the right way through the Lord’s Qur’anic way. And Surah Al- Furqan consists of the educational principles in different areas, like the belief system, thought process and character.